Relativistic bound states in three space-time dimensions in Minkowski space - Gutierrez, C. [UNESP]; Gigante, V.; Frederico, T.; Tomio, Lauro [UNESP] (AIP Publishing, 2016)
With the aim to derive a workable framework for bound states in Minkowski space, we have investigated the Nakanishi perturbative integral representation of the Bethe-Salpeter (BS) amplitude in two-dimensions (2D) in space and time (2+1). The homogeneous BS amplitude, projected onto the light-front plane, is used to derive an equation for the Nakanishi weight function. The formal development is illustrated in detail and applied to the bound system composed by two scalar particles interacting through the exchange of a massive scalar. The explicit forms of the integral equations are obtained in ladder approximation.